2005
DOI: 10.1176/jnp.17.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Electrotherapy Stimulation Reduces Aggression in a Violent Retarded Population: A Preliminary Report

Abstract: Nine aggressive, retarded patients refractory to conventional care at a maximum security hospital were given a 3-month course of cranial electrotherapy stimulation. Aggressive episodes declined 59% from baseline; seclusions were down 72%; restraints were down 58%; and use of prescribed-as-needed sedative medications decreased 53%. The most dramatic change was that of a disorganized, schizophrenic patient whose aggressive episodes declined from 62 to 9, seclusions from 53 to 8, restraints from 9 to 1 and PRNs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Overall, these results were consistent with prior studies that demonstrated the effectiveness of CES on symptoms of anxiety=hyperarousal, irritability, sleep disturbance, and impaired concentration (e.g., Bystritsky, 2009;Gilula & Kirsch, 2005;Kennerly, 2006;Kirsch & Gilula, 2007;Kirsch & Smith, 2004;Smith, 2001;Southworth, 1999) as well as decreased muscle tension, agitation (Childs & Price, 2007), and stress (Giordano, 2006). Thus, the present study supported the use of CES as a treatment for common symptoms seen in PTSD, such as anxiety= hyperarousal, irritability, sleep disturbance, and its impact on performance and satisfaction in daily activities.…”
Section: Symptom Severity In Ptsdsupporting
confidence: 89%
“…Overall, these results were consistent with prior studies that demonstrated the effectiveness of CES on symptoms of anxiety=hyperarousal, irritability, sleep disturbance, and impaired concentration (e.g., Bystritsky, 2009;Gilula & Kirsch, 2005;Kennerly, 2006;Kirsch & Gilula, 2007;Kirsch & Smith, 2004;Smith, 2001;Southworth, 1999) as well as decreased muscle tension, agitation (Childs & Price, 2007), and stress (Giordano, 2006). Thus, the present study supported the use of CES as a treatment for common symptoms seen in PTSD, such as anxiety= hyperarousal, irritability, sleep disturbance, and its impact on performance and satisfaction in daily activities.…”
Section: Symptom Severity In Ptsdsupporting
confidence: 89%
“…The use of electricity and magnetic fields in the biomedical studies, and in particular in the treatment of disturbances of the nervous system, is not a new idea [44][45][46][47]. Nevertheless modern technology and advanced knowledge in the physical-medical field and in the neurosciences has allowed realizing the new biomedical instrument presented in this study.…”
Section: Discussionmentioning
confidence: 99%